One‐stop‐shop with confocal microscopy imaging vs. standard care for surgical treatment of basal cell carcinoma: an open‐label, noninferiority, randomized controlled multicentre trial. (1st September 2017) - Kadouch, D.J.; Elshot, Y.S.; Zupan‐Kajcovski, B.; van Haersma de With, A.S.E.; van der Wal, A.C.; Leeflang, M.; Jóźwiak, K.; Wolkerstorfer, A.; Bekkenk, M.W.; Spuls, P.I.; de Rie, M.A.
Summary: Background: Routine punch biopsies are considered to be standard care for diagnosing and subtyping basal cell carcinoma (BCC) when clinically suspected. Objectives: We assessed the efficacy of a one‐stop‐shop concept using in vivo reflectance confocal microscopy (RCM) imaging as a diagnostic tool vs. standard care for surgical treatment in patients with clinically suspected BCC. Methods: In this open‐label, parallel‐group, noninferiority, randomized controlled multicentre trial we enrolled patients with clinically suspected BCC at two tertiary referral centres in Amsterdam, the Netherlands. Patients were randomly assigned to the RCM one‐stop‐shop (diagnosing and subtyping using RCM followed by direct surgical excision) or standard care (planned excision based on the histological diagnosis and subtype of a punch biopsy). The primary outcome was the proportion of patients with tumour‐free margins after surgical excision of BCC. Results: Of the 95 patients included, 73 (77%) had a BCC histologically confirmed using a surgical excision specimen. All patients (40 of 40, 100%) in the one‐stop‐shop group had tumour‐free margins. In the standard‐care group tumour‐free margins were found in all but two patients (31 of 33, 94%). The difference in the proportion of patients with tumour‐free margins after BCC excision between the one‐stop‐shop group and the standard‐care group was −0·06 (90% confidence interval −0·17−0·01), establishing noninferiority. Conclusions: The proposed new treatment strategy seems suitable in facilitating early diagnosis and direct treatment for patients with BCC, depending on factors such as availability of RCM, size and site of the lesion, patient preference and whether direct surgical excision is feasible.